Grinding kinetics of coal in wet ball-milling using the Taguchi method. Issue 3 (4th March 2022) - Bu, Xiangning; Ma, Guangxi; Peng, Yaoli; Xie, Guangyuan; Zhan, Hanhui; Liu, Baiyang
ABSTRACT: In this study, the Taguchi method was used to study the influence of feed size, ball diameter, pulp density and grinding time on the grinding performance of wet ball-milling. According to P -values, the final ranking of the significance of factors in grinding efficiency was as follows: pulp density > feed size > grinding time > ball diameter. Results of signal-to-noise ratio (S/N ratio) and analysis of variance (ANOVA) indicated that the minimum mass fraction remaining in the top size interval was produced for the −3.0 + 1.0 mm feed size, 75 wt. % pulp density, 50 min grinding time and 35 mm balls. Grinding kinetics of −3.0 + 1.0 mm coal in wet ball-milling were investigated using the breakage rate and primary breakage distribution functions. The deceleration effect for the wet grinding of this coal sample was due to the relatively stronger material (quartz), which had a slower breakage rate compared to the weaker material (organic matter). Moreover, the Mohs' hardness of the material had a significant influence on the parameters of the primary breakage distribution function according to experimental results and literature data. Finally, the morphology and shape of ground particles were analyzed to determine the breakage characteristics.